AXIOLOGICAL VECTOR OF POETICS TRANSFORMATION IN ANTON PAVLOVICH CHEKHOV’S EARLY PROSE - Abdullaeva Ikbola Mokhirovna (Bright Mind Publishing, 2026)
This research provides an in-depth analysis of the axiological (value-oriented) evolution within the early literary corpus of Anton Pavlovich Chekhov (1880–1887). The author posits that the transformation of Chekhov’s poetics during this period is not merely stylistic but fundamentally ontological. By examining the transition from the “Antosha Chekhonte” pseudonym to the mature “Chekhov” the paper identifies a shift from the negative axiology of social satire to a positive existential anthropology. The study utilizes a multidisciplinary approach, blending literary criticism with philosophical value theory, to demonstrate how A.P. Chekhov dismantled the “rank-based” consciousness of the 19th century to establish a new paradigm of human dignity.
Keywords: Axiological paradigm, A.P. Chekhov, poetic transformation, Early prose, ontological shift, ethical debt, existentialism in literature.